Influência de fatores intrínsecos e extrínsecos na motivação de indivíduos adultos com seqüelas de lesões neurológicas - Oliveira, Sabrina Ferreira de (2009)
Motivation is usually defined as an inner strength or will, followed by an action towards a goal. Its importance to rehabilitation is established by its positive relation with better and faster functional recovery. Individuals with pathologies or injuries in the Central Nervous System may present motivational disorders. Apathy is the most common and the least intense motivational disorder. The general purpose of this research is to investigate the factors which would distinguish motivated people with physical disability from those demotivated, by using apathy as a reference of demotivation. The study was conducted in two studies. The first one, dealing with the cultural adaptation of the Apathy Evaluation Scale, and the second using all the tools selected to identify intrinsic and extrinsic factors that would influence the participants´ motivation. 14 participants were selected for the first study and 51 for the second, together with their caretakers. The participants were 33 to 89 years old and presented stroke sequelae, traumatic brain injury, Parkinson's disease and Alzheimer's disease. The caretakers responded to the Apathy Evaluation Scale and the patients completed the general characterization questionnaire, WHOQol-100 World Health Organization Quality of Life (WHOQOL-100) scale and Beck Depression Inventory (BDI). The data was analyzed through SPSS, with descriptive statistics, Pearson correlation test and Student´s t-test (regressive and inferential). The analysis of the Brazilian version of the Apathy Evaluation Scale, obtained in the first study, revealed its suitability to be used in the sample of this investigation. The final results demonstrated that Apathy is significantly correlated with age, degenerative diseases, right hemisphere lesions, general comorbidity, lack of energy, lack of leisure opportunities, and also lack of capacity to undertake physical and cognitive daily activities, and low self-esteem. Differences in self-esteem, work capacity, quality of sleep, day-to-day energy, personal relationship, leisure and physical domains were detected between apathetic and non-apathetic participants. Self-esteem, presence of general comorbidity and work capacity were the main factors to predict apathy. Therefore, both, intrinsic and extrinsic features determine apathy in this kind of population. Drug intervention and familiar guidance may help the rehabilitation professionals increase motivation to functional rehabilitation, which may lead patients to physical, psychological and social benefits.